Research activity does not affect nest predation rates of the Silver-throated Tit, a passerine bird building domed nests - Qian Hu; Ye Wen; Gaoyang Yu; Jiangnan Yin; Haohui Guan; Lei Lv; Pengcheng Wang; Jiliang Xu; Yong Wang; Zhengwang Zhang; Jianqiang Li (Avian Research, 2020)
Abstract Background Research activities have often been thought to potentially influence avian nesting success by increasing nest predation rates. Although recent studies of species building open nests and cavity nests suggest that research disturbance does not generally induce nest predation, whether it is also the case in species building domed-nests remains unknown. In birds, domed-nest species exist in about half of the passerine families, and research disturbance to the domed nests may differ from that to the nests of other types for their different nest structures. Methods We investigated if research activities affected nest predation rate by analyzing the relationships of the daily nest survival rate with the research activities at the egg and nestling stages of a domed-nest species, the Silver-throated Tit (Aegithalos glaucogularis). Results Our results showed that nest daily survival rate was significantly affected by the laying date and nest age during the egg stage, and by the hatching date only during the nestling stage. By contrast, there were no significant effects of research activities, in terms of visiting nests and filming nests, on the nest survival of the Silver-throated Tit at both the egg and nestling stages. Conclusions Our results coincide with the findings in species building other types of nests that research activities do not always have negative effects on avian nesting success.